Strategi Perlindungan Anak Usia Dini pada Kesiapan Masa Transisi dari PAUD ke Sekolah Dasar yang Menyenangkan - Imrotul Ummah; Miftakhul Jannah; Yes Matheos Lasarus Malaikosa (Jurnal Pendidikan Dasar Islam, 2024)
Children need the right support to face the changes they are going through, both the way they learn, socialize and adapt to different routines. This research is based on a literature review conducted by finding and managing various sources of information that correspond to the central issues of the topic. Obtained from the Journal of related professions. Literature reviews analyze, evaluate, and summarize research findings, theory, and practice within a specific focus area. The results of this study generally indicate that there are four strategies for early childhood protection that are available and feasible for a pleasant transition from early childhood to elementary school. These efforts include (1) creating child-friendly schools and (2) providing basic training for the strengthening of life skills (lifeskill) (3) strengthening foundation skills, and (4) collaboration of parents, schools, and communities in collaboration and communication between children, families, schools, and communities, which is part of the preparation and positive transition is an important element in promoting and supporting the transition of early childhood to elementary school fun.